Comparing blends and blocks: Synthesis of partially fluorinated diblock polythiophene copolymers to investigate the thermal stability of optical and morphological properties - Boufflet, Pierre; Wood, Sebastian; Wade, Jessica; Fei, Zhuping; Kim, Ji-Seon; Heeney, Martin (Beilstein Journal of Organic Chemistry, 2016)
The microstructure of the active blend layer has been shown to be a critically important factor in the performance of organic solar devices. Block copolymers provide a potentially interesting avenue for controlling this active layer microstructure in solar cell blends. Here we explore the impact of backbone fluorination in block copolymers of poly(3-octyl-4-fluorothiophene)s and poly(3-octylthiophene) (F-P3OT-b-P3OT). Two block co-polymers with varying block lengths were prepared via sequential monomer addition under Kumada catalyst transfer polymerisation (KCTP) conditions. We compare the behavior of the block copolymer to that of the corresponding homopolymer blends. In both types of system, we find the fluorinated segments tend to dominate the UV–visible absorption and molecular vibrational spectral features, as well as the thermal behavior. In the block copolymer case, non-fluorinated segments appear to slightly frustrate the aggregation of the more fluorinated block. However, in situ temperature dependent Raman spectroscopy shows that the intramolecular order is more thermally stable in the block copolymer than in the corresponding blend, suggesting that such materials may be interesting for enhanced thermal stability of organic photovoltaic active layers based on similar systems.
Keywords: conjugated block-copolymer synthesis; fluorination; microphase stabilization; polythiophene; temperature-dependent Raman spectroscopy

(untitled) - Robb, M. J.; Ku, S.-Y.; Hawker, C. J. (Adv. Mater., 2013)

(untitled) - Lee, Y.; Gomez, E. D. (Macromolecules, 2015)

(untitled) - Yassar, A.; Miozzo, L.; Gironda, R.; Horowitz, G. (Prog. Polym. Sci., 2013)

(untitled) - Darling, S. B. (Energy Environ. Sci., 2009)

(untitled) - Verswyvel, M.; Steverlynck, J.; Hadj Mohamed, S.; Trabelsi, M.; Champagne, B.; Koeckelberghs, G. (Macromolecules, 2014)

(untitled) - Segalman, R. A.; McCulloch, B.; Kirmayer, S.; Urban, J. J. (Macromolecules, 2009)

(untitled) - He, M.; Qiu, F.; Lin, Z. (J. Mater. Chem., 2011)

(untitled) - Proctor, C. M.; Kuik, M.; Nguyen, T.-Q. (Prog. Polym. Sci., 2013)

(untitled) - Shaw, P. E.; Ruseckas, A.; Samuel, I. D. W. (Adv. Mater., 2008)

(untitled) - Ku, S.-Y.; Brady, M. A.; Treat, N. D.; Cochran, J. E.; Robb, M. J.; Kramer, E. J.; Chabinyc, M. L.; Hawker, C. J. (J. Am. Chem. Soc., 2012)

(untitled) - Yamada, I.; Takagi, K.; Hayashi, Y.; Soga, T.; Shibata, N.; Toru, T. (Int. J. Mol. Sci., 2010)

(untitled) - Suspène, C.; Miozzo, L.; Choi, J.; Gironda, R.; Geffroy, B.; Tondelier, D.; Bonnassieux, Y.; Horowitz, G.; Yassar, A. (J. Mater. Chem., 2012)

(untitled) - Mulherin, R. C.; Jung, S.; Huettner, S.; Johnson, K.; Kohn, P.; Sommer, M.; Allard, S.; Scherf, U.; Greenham, N. C. (Nano Lett., 2011)

(untitled) - Gao, D.; Hollinger, J.; Seferos, D. S. (ACS Nano, 2012)

(untitled) - Lai, Y.-C.; Ohshimizu, K.; Takahashi, A.; Hsu, J.-C.; Higashihara, T.; Ueda, M.; Chen, W.-C. (J. Polym. Sci., Part A: Polym. Chem., 2011)

(untitled) - Zhang, Q.; Cirpan, A.; Russell, T. P.; Emrick, T. (Macromolecules, 2009)

(untitled) - Nakabayashi, K.; Mori, H. (Macromolecules, 2012)

(untitled) - Guo, C.; Lin, Y.-H.; Witman, M. D.; Smith, K. A.; Wang, C.; Hexemer, A.; Strzalka, J.; Gomez, E. D.; Verduzco, R. (Nano Lett., 2013)

(untitled) - McNeill, C. R. (Energy Environ. Sci., 2012)

(untitled) - Sivula, K.; Ball, Z. T.; Watanabe, N.; Fréchet, J. M. J. (Adv. Mater., 2006)

(untitled) - Renaud, C.; Mougnier, S.-J.; Pavlopoulou, E.; Brochon, C.; Fleury, G.; Deribew, D.; Portale, G.; Cloutet, E.; Chambon, S.; Vignau, L.; Hadziioannou, G. (Adv. Mater., 2012)

(untitled) - Segalman, R. A. (Mater. Sci. Eng., R, 2005)

(untitled) - Bates, F. S.; Fredrickson, G. H. (Phys. Today, 1999)

(untitled) - Locke, J. R.; McNeil, A. J. (Macromolecules, 2010)

(untitled) - Hollinger, J.; DiCarmine, P. M.; Karl, D.; Seferos, D. S. (Macromolecules, 2012)

(untitled) - Palermo, E. F.; McNeil, A. J. (Macromolecules, 2012)

(untitled) - Iovu, M. C.; Sheina, E. E.; Gil, R. R.; McCullough, R. D. (Macromolecules, 2005)

(untitled) - Bryan, Z. J.; McNeil, A. J. (Macromolecules, 2013)

(untitled) - Hollinger, J.; Jahnke, A. A.; Coombs, N.; Seferos, D. S. (J. Am. Chem. Soc., 2010)

(untitled) - Kozycz, L. M.; Gao, D.; Hollinger, J.; Seferos, D. S. (Macromolecules, 2012)

(untitled) - Stefan, M. C.; Bhatt, M. P.; Sista, P.; Magurudeniya, H. D. (Polym. Chem., 2012)

(untitled) - Kiriy, A.; Senkovskyy, V.; Sommer, M. (Macromol. Rapid Commun., 2011)

(untitled) - Kim, Y.-J.; Cho, C.-H.; Paek, K.; Jo, M.; Park, M.-k.; Lee, N.-E.; Kim, Y.-j.; Kim, B. J.; Lee, E. (J. Am. Chem. Soc., 2014)

(untitled) - Sommer, M.; Komber, H.; Huettner, S.; Mulherin, R.; Kohn, P.; Greenham, N. C.; Huck, W. T. S. (Macromolecules, 2012)

(untitled) - Senkovskyy, V.; Tkachov, R.; Beryozkina, T.; Komber, H.; Oertel, U.; Horecha, M.; Bocharova, V.; Stamm, M.; Gevorgyan, S. A.; Krebs, F. C.; Kiriy, A. (J. Am. Chem. Soc., 2009)

(untitled) - Paoprasert, P.; Spalenka, J. W.; Peterson, D. L.; Ruther, R. E.; Hamers, R. J.; Evans, P. G.; Gopalan, P. (J. Mater. Chem., 2010)

(untitled) - Awada, H.; Medlej, H.; Blanc, S.; Delville, M.-H.; Hiorns, R. C.; Bousquet, A.; Dagron-Lartigau, C.; Billon, L. (J. Polym. Sci., Part A: Polym. Chem., 2014)

(untitled) - Awada, H.; Mezzasalma, L.; Blanc, S.; Flahaut, D.; Dagron-Lartigau, C.; Lyskawa, J.; Woisel, P.; Bousquet, A.; Billon, L. (Macromol. Rapid Commun., 2015)

(untitled) - Okamoto, K.; Luscombe, C. K. (Polym. Chem., 2011)

(untitled) - Olsen, B. D.; Segalman, R. A. (Mater. Sci. Eng., R, 2008)

(untitled) - Boufflet, P.; Han, Y.; Fei, Z.; Treat, N. D.; Li, R.; Smilgies, D.-M.; Stingelin, N.; Anthopoulos, T. D.; Heeney, M. (Adv. Funct. Mater., 2015)

(untitled) - Fei, Z.; Boufflet, P.; Wood, S.; Wade, J.; Moriarty, J.; Gann, E.; Ratcliff, E. L.; McNeill, C. R.; Sirringhaus, H.; Kim, J.-S.; Heeney, M. (J. Am. Chem. Soc., 2015)

(untitled) - Chen, T.-A.; Wu, X.; Rieke, R. D. (J. Am. Chem. Soc., 1995)

(untitled) - Koch, F. P. V.; Smith, P.; Heeney, M. (J. Am. Chem. Soc., 2013)

(untitled) - Loewe, R. S.; Khersonsky, S. M.; McCullough, R. D. (Adv. Mater., 1999)

(untitled) - Loewe, R. S.; Ewbank, P. C.; Liu, J.; Zhai, L.; McCullough, R. D. (Macromolecules, 2001)

(untitled) - Lohwasser, R. H.; Thelakkat, M. (Macromolecules, 2011)

(untitled) - Tkachov, R.; Senkovskyy, V.; Komber, H.; Kiriy, A. (Macromolecules, 2011)

(untitled) - Boyd, S. D.; Jen, A. K.-Y.; Luscombe, C. K. (Macromolecules, 2009)

(untitled) - Liu, J.; Loewe, R. S.; McCullough, R. D. (Macromolecules, 1999)

(untitled) - Wong, M.; Hollinger, J.; Kozycz, L. M.; McCormick, T. M.; Lu, Y.; Burns, D. C.; Seferos, D. S. (ACS Macro Lett., 2012)

(untitled) - Clark, J.; Silva, C.; Friend, R. H.; Spano, F. C. (Phys. Rev. Lett., 2007)

(untitled) - Yamagata, H.; Pochas, C. M.; Spano, F. C. (J. Phys. Chem. B, 2012)

(untitled) - Martin, T. P.; Wise, A. J.; Busby, E.; Gao, J.; Roehling, J. D.; Ford, M. J.; Larsen, D. S.; Moulé, A. J.; Grey, J. K. (J. Phys. Chem. B, 2013)

(untitled) - Baghgar, M.; Labastide, J. A.; Bokel, F.; Hayward, R. C.; Barnes, M. D. (J. Phys. Chem. C, 2014)

(untitled) - Schubert, M.; Dolfen, D.; Frisch, J.; Roland, S.; Steyrleuthner, R.; Stiller, B.; Chen, Z.; Scherf, U.; Koch, N.; Facchetti, A.; Neher, D. (Adv. Energy Mater., 2012)

(untitled) - Fabiano, S.; Chen, Z.; Vahedi, S.; Facchetti, A.; Pignataro, B.; Loi, M. A. (J. Mater. Chem., 2011)

(untitled) - Mori, D.; Benten, H.; Kosaka, J.; Ohkita, H.; Ito, S.; Miyake, K. (ACS Appl. Mater. Interfaces, 2011)

(untitled) - Ho, C.-C.; Liu, Y.-C.; Lin, S.-H.; Su, W.-F. (Macromolecules, 2012)

(untitled) - Campo, B. J.; Bevk, D.; Kesters, J.; Gilot, J.; Bolink, H. J.; Zhao, J.; Bolsée, J.-C.; Oosterbaan, W. D.; Bertho, S.; D’Haen, J.; Manca, J.; Lutsen, L.; et al. (Org. Electron., 2013)

(untitled) - Zhang, Y.; Tajima, K.; Hirota, K.; Hashimoto, K. (J. Am. Chem. Soc., 2008)

(untitled) - Noriega, R.; Rivnay, J.; Vandewal, K.; Koch, F. P. V.; Stingelin, N.; Smith, P.; Toney, M. F.; Salleo, A. (Nat. Mater., 2013)

(untitled) - Spano, F. C. (Acc. Chem. Res., 2010)

(untitled) - Wood, S.; Garnett, O.; Tokmoldin, N.; Tsoi, W. C.; Haque, S. A.; Kim, J.-S. (Faraday Discuss., 2014)

(untitled) - Tsoi, W. C.; James, D. T.; Kim, J. S.; Nicholson, P. G.; Murphy, C. E.; Bradley, D. D. C.; Nelson, J.; Kim, J.-S. (J. Am. Chem. Soc., 2011)